Understanding mobile banking individual performance - Tam, Carlos (2017)
Tam, C., & Oliveira, T. (2017). Understanding mobile banking individual performance: The DeLone & McLean model and the moderating effects of individual culture. Internet Research, 27(3), 538-562. https://doi.org/10.1108/IntR-05-2016-0117 ---%ABS2%